Posttraumatic stress disorder and total amyloid burden and amyloid‐β 42/40 ratios in plasma: Results from a pilot study of World Trade Center responders. Issue 1 (28th February 2019) - Clouston, Sean A.P.; Deri, Yael; Diminich, Erica; Kew, Richard; Kotov, Roman; Stewart, Candace; Yang, Xiaohua; Gandy, Sam; Sano, Mary; Bromet, Evelyn J.; Luft, Benjamin J.
Abstract: Introduction: Chronic posttraumatic stress disorder (PTSD) is associated with poor memory and increased burden of various degenerative cerebral neuropathologies. The goal of this pilot study was to determine whether PTSD was associated with changes in plasma‐based neuropathological biomarkers of neurodegeneration among World Trade Center (WTC) responders. Methods: Thirty‐four WTC responders had blood drawn and flash‐frozen within 15 minutes of retrieval. PTSD symptoms were assessed at that time. Age, sex, and WTC exposure duration were obtained from medical records. Plasma was assayed in duplicate using an ultra‐sensitive single‐molecule enzyme‐linked immunosorbent assay to examine the distribution of amyloid‐β (Aβ) 42/40 ratios, total Aβ, total tau, and neurofilament light (NfL). The comparison group was drawn from a bank of healthy controls collected and assayed at the same facility. Results: The average age of WTC responders at blood draw was 53 years. Half were PTSD positive (PTSD+) as indicated by symptom severity. WTC responders had lower Aβ42/Aβ40 ratios but higher total tau and NfL levels in the plasma than healthy controls. PTSD+ status was associated with lower plasma Aβ load and higher Aβ42/Aβ40 ratios. Discussion: Findings suggest that PTSD may be associated with alterations in plasma markers related to Aβ, tau, and NfL, highlighting the potential association between PTSD status and neurodegenerative neuropathology in WTC responders.